Investigating Intercultural Teaching Competence among Moroccan Teachers in Tertiary Education - Mouhssine Echcharfy (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2019)
Intercultural learning is a new pedagogy that encourages learners to establish relationships between their own culture and the other culture, managing dysfunctions and mediating differences. These skills and others will enable learners to develop intercultural competence and help them become intercultural speakers/mediators (Byram, 1997). However, learners’ intercultural competence cannot be developed without an appropriate intervention and guidance on the part of the teacher who represents a central element in the intercultural learning process. Thus, the issue at stake is the degree to which teachers demonstrate knowledge of skills and competencies they need for the development of students’ intercultural competence and awareness. In this respect, the present study is an attempt to explore the extent to which the teachers’ competencies and skills meet the specifications formulated in the literature regarding intercultural teaching competence. It included 25 Moroccan university teachers who have already taught culture at the university. In line with the objective of the study, a five-point Likert scale questionnaire was adopted as a major data collection procedure. The results revealed that the majority of Moroccan university teachers demonstrated negative attitudes towards and lack of awareness regarding the intercultural teaching competencies provided. It also turned out that the majority of teachers’ competencies do not meet the specifications formulated in the literature, regarding intercultural teaching competence. In light of the results obtained, several implications are derived from the study for decision makers and teachers.